Clinical Profile, Immediate Outcome and Predictors of Poor Outcome of Children in Pediatric Intensive Care Unit with Sepsis - Wagley Poudel, Bulu; Shrestha, Pun Narayan; Shrestha, Sanjeet Kumar; Malla, Sadikshya Shah; Rayamajhi, Ajit (Journal of Institute of Medicine Nepal, 2024)
Introduction Sepsis remains a major cause of death in children with death rate ranging from 5% in developed countries to 35% in developing countries. However, data on the predictive factors for poor outcome particularly in developing countries, remain limited. So this study aims to evaluate the clinical profile, immediate outcome and factors associated with poor outcome of the children with sepsis. Methods This retrospective study was conducted in the Pediatric Intensive Care Unit (PICU) at Kanti Children Hospital, Kathmandu. Medical records of patients aged 30 days to 14 years, diagnosed with sepsis based on clinical and laboratory parameters and admitted to the PICU between April 2024 to September 2024 were analyzed. The clinical features, outcome in the form of discharge or death during the hospital stay and factors effecting the poor outcome were tabulated and the data analysis was done by SPSS version 21. Results The total number of patient enrolled in the study were 53. The mean age of the patient was (3.49±0.183) yrs. Among them 31/53(58 %) were male and 22/53(42%) were female. Among them 42/53(79.25%) were Hindus 5/53(9.43%) were Muslims 4/53(7.54%) Buddhist and 2/53 (3.77%) Christian. The most common presenting symptom was fever observed in 50/53(94.4%) of cases. The mortality rate for sepsis was (14/53)26.41% which is statistically significant. Predictors of poor outcome included were the need for dialysis (p=0.016), the presence of Central Nervous System disease (p=0.001), the use of mechanical ventilation (p=0.00), the use of ionotropic support (p=0.010) and elevated D-dimer levels (p=0.036). Conclusion Fever was the most common symptom of sepsis with a mortality rate of 26.41%. Key predictors of poor outcome included the need of dialysis, presence of CNS disease, mechanical ventilation, the use of ionotropic support and elevated D-dimer level.